Optimized Oxidation Temperature Enhances OER Performance of IrO₂‐Loaded SnO₂ Nanofibers – Role of Charge Carrier Percolation Pathways - Melisande Kost; Jean Felix Dushimineza; Knut Müller‐Caspary; Thomas Bein (Advanced Materials Interfaces)
Abstract The potential for reducing iridium content in large‐scale proton‐exchange membrane (PEM) electrolysis is examined using a fibrous support morphology to enhance electron percolation. Focusing on high activity, stability, and conductivity, ultra‐small, interconnected IrOx/IrO2 nanoparticles anchored to electrospun SnO2 nanofibers (IrOx/IrO2@SnO2) are investigated, with particular attention to the crystallinity of the iridium phase. Scanning transmission electron microscopy (STEM), conducted both before and after use as an electrocatalyst for the oxygen evolution reaction (OER), reveals how the oxidation temperature impacts the crystallinity and stability of the iridium oxide phase. The results suggest that further reductions in iridium content may be achieved by optimizing synthesis parameters. Here, the highest iridium utilization is achieved at an oxidation temperature of 375 °C, with improved conductivity and electrochemical activity. Transmission electron microscopy (TEM) indicates that higher oxidation temperatures result in fragmentation of conduction pathways, negatively affecting catalyst performance. Furthermore, TEM reveals the onset of IrO₂ crystallization between 365 and 375 °C, with cyclic voltammetry (CVA) emphasizing the critical role of conductivity in ensuring efficient charge carrier transport to active sites. This study not only deepens the understanding of iridium‐based catalysts but also identifies practical strategies to enhance cost‐effectiveness and efficiency in PEM electrolysis technologies.